Optimizing surgical outcomes in bladder cancer patients undergoing radical cystectomy - Pere, Maria; Amantakul, Akara; Sriplakich, Supon; Tarin, Tatum (Frontiers in Surgery, 2023)
Purpose: To evaluate predictors of high-quality surgery and their effect on surgical outcomes in patients with bladder cancer undergoing radical cystectomy. Evidence Acquisition: A systematic and thorough review was performed to identify the most recent literature on current optimal management and predictors of high-quality surgery for patients undergoing radical cystectomy. Conclusions: Muscle-invasive bladder cancer is an aggressive cancer requiring efficient and high-quality surgery in order to achieve the best oncological outcomes. Negative surgical margins, number of lymph nodes resected, lymph node dissection template, and surgical volume have been associated with improved oncologic outcomes. Robotic radical cystectomy continues to evolve and recent randomized controlled trials have shown that oncological outcomes are non-inferior when compared to the open technique. Regardless of approach, surgical technique should continually be evaluated and refined to optimize outcomes in patients undergoing radical cystectomy.